Liver radiofrequency ablation compromises the biological gut barrier. (January 2014) - Ypsilantis, P; Lambropoulou, M; Kourkoutas, I; Pechlivanis, A; Simopoulos, C
Aim: Liver radiofrequency ablation (RFA) has been shown to disrupt the mechanical component of the gut barrier. The aim of the present study was to investigate the consequences of liver RFA on the biological gut barrier in terms of the effects of bile production rate and bowel inflammatory state on intestinal microflora balance. Method: A total of 25 New Zealand rabbits were assigned to five groups ( n = 5 per group): group CBD: subjected to common bile duct (CBD) extracorporeal bypass; group CBD-RFA: subjected to CBD bypass plus one session of open liver RFA; group RFA: subjected to liver RFA; group sham: subjected to sham operation; and group TBD: subjected to total bile deviation (TBD). In groups CBD and CBD-RFA, bile production rate was assessed for 48 h. In groups sham and RFA, measurement of biliary glycine conjugates of cholic and deoxycholic acid levels, histopathologic examination of the non-ablated liver tissue, morphometric analysis, and histopathologic examination of the terminal ileum and microbiological analysis of fecal and tissue samples collected from the jejunum and the cecum (and in group TBD) were performed at 48 h post-operation. Results: One session of liver RFA resulted in ablation of 18.7 ± 2.7% of liver weight. Following liver RFA, bile production rate was reduced, while the levels of biliary bile salts were not affected. There was mild injury of the non-ablated liver parenchyma, mild intestinal wall inflammation, intestinal mucosa atrophy, and intestinal microbial population overgrowth. Conclusion: Reduced in bile production and mild bowel inflammation secondary to liver RFA impaired the biological gut barrier as manifested by intestinal microflora imbalance.